2014
DOI: 10.1682/jrrd.2013.10.0221
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-method approach to veteran satisfaction with pain education

Abstract: Abstract-Patient education is a central component in highquality integrated care of patients with chronic pain. The current study assessed patients' satisfaction with a 12 wk "Pain Education School" program within the initial 2 yr phase of implementation. A mixed-method treatment outcome design was used. A sample of 219 veterans between November 6, 2009, and January 20, 2012, was evaluated. Quantitative findings suggest that patients reported learning "new and useful" information (mean = 4.62 +/-0.82), perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
1
6
1
Order By: Relevance
“…Past research has shown that veterans found specific modules (acupuncture and medication management) to be more relevant, and found other modules (tobacco cessation and hypnosis) to be less fitting. 64 However, the current study did not find that subject matter from any of the classes had any effect on attendance.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Past research has shown that veterans found specific modules (acupuncture and medication management) to be more relevant, and found other modules (tobacco cessation and hypnosis) to be less fitting. 64 However, the current study did not find that subject matter from any of the classes had any effect on attendance.…”
Section: Discussioncontrasting
confidence: 82%
“…Past research has examined what themes veterans commented as being barriers to attendance in the pain education program, and found that veterans either reported not having any barriers (24%) or noted travel (24%), finances (21%), or other illness (18%) as being obstacles. 64 Other studies investigating military personnel have found the most frequently reported reason for missing appointments was administrative error (including believing their appointment was on another date, having cancelled the appointment, and not knowing they had an appointment). 65 Furthermore, due to limitations of this archival collection, demographics (e.g., gender differences 15,51 ) and other individual barriers to care (e.g., distance from the facility and/or finances 66 ) were not able to be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative methods enable researchers to gain a broader understanding of human experiences, attitudes, and processes through an emphasis on participant perceptions [1618]. Past research has highlighted the added value of this methodology in understanding the subjective experience of pain [1922]. A recent randomized controlled trial found a concordance rate of less than 50% between quantitative questionnaire and qualitative interview data [23].…”
Section: Introductionmentioning
confidence: 99%
“…Seven articles met the inclusion criteria. Examples of studies excluded were the articles in which there is no clear information on duration of pain of participants 31,32 ; education was combined with other interventions 33,34 ; and to understand their condition, be active participants in their treatment, and comply with therapeutic interventions. 23 Also, education is central in establishing and maintaining the positive behaviors needed for effectively managing the chronic pain.…”
Section: Stage Three: Study Selectionmentioning
confidence: 99%